Stress activation of Bacillus subtilis sigma B can occur in the absence of the sigma B negative regulator RsbX. - Voelker, U (1997)
Environmental stress activates sigma B, the general stress response sigma factor of Bacillus subtilis, by a pathway that is negatively controlled by the RsbX protein. To determine whether stress activation of sigma B occurs by a direct effect of stress on RsbX, we constructed B. subtilis strains which synthesized various amounts of RsbX or lacked RsbX entirely and subjected these strains to ethanol stress. Based on the induction of a sigma B-dependent promoter, stress activation of sigma B can occur in the absence of RsbX. Higher levels of RsbX failed to detectably influence stress induction, but reduced levels of RsbX resulted in greater and longer-lived sigma B activation. The data suggest that RsbX is not a direct participant in the sigma B stress induction process but rather serves as a device to limit the magnitude of the stress response.